A survey on efficiency and profitable trading opportunities in cryptocurrency markets - Nikolaos A. Kyriazis (Journal of Risk and Financial Management, 2019)
This study conducts a systematic survey on whether the pricing behavior of cryptocurrencies is predictable. Thus, the Efficient Market Hypothesis is rejected and speculation is feasible via trading. We center interest on the Rescaled Range (R/S) and Detrended Fluctuation Analysis (DFA) as well as other relevant methodologies of testing long memory in returns and volatility. It is found that the majority of academic papers provides evidence for inefficiency of Bitcoin and other digital currencies of primary importance. Nevertheless, large steps towards efficiency in cryptocurrencies have been traced during the last years. This can lead to less profitable trading strategies for speculators.
Keywords: G11; G12; G15; E4; 330; survey; bitcoin; cryptocurrency; efficient market hypothesis